Studi Kasus Penerapan Pijat Refleksi Kaki terhadap Perubahan Tekanan Darah pada Wanita dengan Hipertensi - Wanda Khumairoh; Sumrahadi Sumrahadi; Sestramita Sestramita (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Hypertension remains one of the most prevalent non-communicable diseases and a leading risk factor for cardiovascular morbidity. Alongside pharmacological management, complementary non-pharmacological interventions are increasingly explored in nursing practice to support blood pressure control. Foot reflexology is considered a relaxation-based therapy that may contribute to hemodynamic stabilization. This study aimed to examine changes in blood pressure among women with hypertension following the application of foot reflexology therapy. A descriptive case study design was employed involving two female participants diagnosed with hypertension. The intervention consisted of 20-minute foot reflexology sessions administered each afternoon for three consecutive days. Blood pressure was measured before and after each session, and the outcomes were analyzed descriptively using Mean Arterial Pressure (MAP) to observe overall trends. Both participants demonstrated reductions in systolic and diastolic blood pressure across the intervention period, with MAP values showing a gradual decline over three days. These findings suggest that foot reflexology may induce relaxation and contribute to short-term reductions in blood pressure among women with hypertension. Although limited to a small case sample, the results indicate the potential of foot reflexology as a complementary intervention within community nursing practice and highlight the need for further studies with larger samples and controlled designs.